Mathematical model of seismic signal, as a flow of physically non realizable single seismic waves - Mostovoy, V.S.; Mostovoyi, S.V. (Геофизический журнал, 2016)
The new conception of seismic data analysis is proposed. It is based on preliminary studying of seismic background. Its characteristics are a base for using mathematical models of non realizable seismic signals. The specific mathematical model of the seismic signal is proposed as well. The peculiarity of the model is that it allows you to simulate the flow of seismic waves of different classes each of them appears in the stream with specific time delay. This process takes place against the micro-seismic background noise. It is natural to model the flow of signals by the physically realizable signal. It means those signals which do not have a trace in prehistory. But this representation of the signal is unacceptable for two reasons. The first one is related to the smoothness of the signal at the time of its appearance on the seismic record. The second one is related to the fact that the fade of the signal in the noise does not allow us to determine the time of its appearance on the record accurately. The latter circumstance does not leave us the possibility to simulate the time of the signal occurrence by using the determined value. Therefore, the time of occurrence of the signal is simulated by random variable with variance depending on the level of micro-seismic background. We introduce the notion of generalized seismic signal as a function of time and of the vector of parameters, which determine its shape, the energy, the place in flow of the other signals, spectral characteristics, and in general behavior in the entire history of its existence. Any widely spread seismic signal models used in practice are a particular case of this one. Or in a more rigorous approach to the definition the different particular cases of the signals classes are transformed into the different hyper-planes into space of parameters. Запропоновано нову концепцію аналізу сейсмічних даних. Вона базується на попередньому вивченні сейсмічного фону. Для його параметризації використовується математична модель з фізично нездійсненними сигналами. Також пропонується специфічна математична модель самого сейсмічного сигналу. Особливість моделі полягає в тому, що вона дозволяє симулювати сейсмічні хвилі різними класами сигналів, кожен з яких з’являється в потоці зі своєю тимчасовою затримкою. Цей процес розглядається на мікросейсмічному фоні. Природно моделювати потік фізично здійсненними сигналами. Мається на увазі, що сигнали не мають передісторії. Але таке уявлення сигналу неприйнятно з двох причин. Перша пов'язана з гладкістю сигналу в точці його появи на сейсмічному записі. Друга пов'язана з тим, що на фоні сейсмічного шуму не можливо чітко виділити час вступу сигналу. Остання обставина не дає можливості отримати точний детермінований час вступу сигналу. Тому час вступу сигналу представляється як випадкова величина з довірчим інтервалом, що залежить від рівня мікросейсмічних шуму. Поняття узагальненого сейсмічного сигналу представлено як функцію часу і вектора параметрів, які визначають його форму, енергію, місце в потоці інших сигналів, його спектральні характеристики і в цілому його поведінку в усій історії його існування. Будь-яка широко поширена модель сейсмічного сигналу є окремим випадком запропонованої моделі. Або, більш строго, будь-який інший клас широко відомих моделей сейсмічного сигналу є гіперплощиною в просторі параметрів запропонованої моделі.